The Impact of Earning Surprise on Return and Volatility : A Comparative study between US and Australia using tick by tick data - Zaeem, Faz (2015)
This research aims to evaluate and comparative the impact of earnings surprises on stock returns and volatility using high frequency data from stock markets in Australia and United States of America. Findings indicate that the correlation between earnings surprise and stock returns and volatility is statistically significant in both markets. US stocks tend to respond more strongly to negative earnings surprises as compared to Australian stocks due to varying corporate governance and legal environments in the two countries. Within-day returns for stocks in both countries register mild responses to earnings surprise. Additionally, it is observed that earnings surprise tends to have a greater impact on stock volatility in the United States relative to the Australian market. The results also further validate the contribution of earnings forecasts in valuation of equity prices.